Role of Extension: an Effort and Guarantee to Protect Human Rights in Food Security - Lina Asnamawati; Is Eka Herawati; Yuliawati Yuliawati; Timbul Rasoki (UNIVED Press, Dehasen University Bengkulu, 2023)
Agricultural extension workers are expected to be able to increase farmer participation in collaborating by participating in work program activities and supporting the work program so that the expected goals can be achieved. Agricultural extension workers have a strategic role in increasing the income of farming communities. The issue of food security is not only in Indonesia, in other parts of the world the issue of food security is one of the priorities of world countries. Food is the most important basic human need and its fulfillment is part of the human rights guaranteed in the 1945 Constitution of the Republic of Indonesia as a basic component for creating quality human resources. Realizing food security through agricultural extension as an agricultural country that has abundant soil fertility and local potential. The role of extension is very important to help increase agricultural productivity, support national food security and create farmer welfare. In order to examine several factors and the role of counseling that can support human rights in food security, the researchers conducted a study using the Systematic Literature Review (SLR) method. Data analysis was done using Microsoft Excel and the Bibliometric application to capture global trends from existing research. Data collection was carried out using the Prism Protocol. An in-depth analysis was conducted on 30 articles that discussed the role of extension workers in realizing food security. Based on the research results, it is proposed that the role of extension workers needs to be increased as a determinant of welfare for farmers. The researcher recommends that there should be strategic efforts so that extension agents play a more effective role for small-scale farmers to achieve food security.